Protecting against address space layout randomisation (ASLR) compromises and return-to-libc attacks using network intrusion detection systems - Day, David J; Zhao, Zheng-Xu (Machine intelligence research (Print), 2011)
Writable XOR executable (W⊕X) and address space layout randomisation (ASLR) have elevated the understanding necessary to perpetrate buffer overflow exploits[1]. However, they have not proved to be a panacea[1–3], and so other mechanisms, such as stack guards and prelinking, have been introduced. In this paper, we show that host-based protection still does not offer a complete solution. To demonstrate the protection inadequacies, we perform an over the network brute force return-to-libc attack against a preforking concurrent server to gain remote access to a shell. The attack defeats host protection including W⊕X and ASLR. We then demonstrate that deploying a network intrusion detection systems (NIDS) with appropriate signatures can detect this attack efficiently.